2013
DOI: 10.1016/j.nicl.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain morphometry in carpal tunnel syndrome is associated with median nerve pathology

Abstract: Objective Carpal tunnel syndrome (CTS) is a common median nerve entrapment neuropathy characterized by pain, paresthesias, diminished peripheral nerve conduction velocity (NCV) and maladaptive functional brain neuroplasticity. We evaluated structural reorganization in brain gray (GM) and white (WM) matter and whether such plasticity is linked to altered median nerve function in CTS. Methods We performed NCV testing, T1-weighted structural MRI, and diffusion tensor imaging (DTI) in 28 CTS and 28 age-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 42 publications
1
45
0
1
Order By: Relevance
“…Our previous functional MRI results showed that while ipsilesional S1-hand area is deactivated by local acupuncture, ipsilesional S1-leg area is activated by distal acupuncture (Maeda et al, 2013b). Thus, clinically-relevant fractional anisotropy changes for both local and distal acupuncture were not diffusely distributed throughout S1-adjacent white matter, but were instead localized to areas adjacent to S1 subregions specifically targeted by wrist versus leg acupuncture.…”
Section: Discussionmentioning
confidence: 88%
“…Our previous functional MRI results showed that while ipsilesional S1-hand area is deactivated by local acupuncture, ipsilesional S1-leg area is activated by distal acupuncture (Maeda et al, 2013b). Thus, clinically-relevant fractional anisotropy changes for both local and distal acupuncture were not diffusely distributed throughout S1-adjacent white matter, but were instead localized to areas adjacent to S1 subregions specifically targeted by wrist versus leg acupuncture.…”
Section: Discussionmentioning
confidence: 88%
“…43 Correlation analyses associated cortical thickness and clinical variables (NCV and BCTQ), significant at P # 0.05. In addition, as our previous study directly contrasted structural brain data from subjects with CTS (a subset, N 5 20, of the larger sample, N 5 59, reported herein) vs healthy controls and reported significant gray matter volume differences between patients with CTS and healthy adults, 30 this study did not directly contrast CTS data with healthy controls. In this study, healthy control subject data from significant clusters identified above were used to descriptively aid interpretation of how differences between CTS-pain and CTS-paresthesia cortical thickness relate to cortical thickness measures in age-matched and sex-matched healthy adults.…”
Section: Magnetic Resonance Imaging Data Analysismentioning
confidence: 85%
“…We found that reduced gray matter volume within the S1 hand area contralateral to the more affected hand was associated with median nerve sensory velocity. 30 Other studies have also demonstrated reduced gray matter volume in patients with chronic pain 1 and reduced cortical thickness in cases of more severe peripheral deafferentation, such as peripheral nerve transection. 53 However, the association between such structural brain changes and specific symptomatology or peripheral nerve function in patients with chronic neuropathic pain is not well understood.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The patients with CTS had an increased thumb-index finger correlation only during the lowering phase, which may be because the central controller minimized the degree of freedom by augmenting the relative roles of the thumb and index finger [25]. Furthermore, reorganization of the brain structures was found to correlate with the nerve conduction velocity in patients with CTS, and this was thought to be a secondary adaption to the peripheral nerve impairments [31]. However, more research is needed to link the relationships between the motor performance of the distal hand and central neural activities to verify the related control mechanism.…”
Section: Discussionmentioning
confidence: 99%